Lactobacillus species as biomarkers and agents that can promote various aspects of vaginal health - Petrova, Mariya I.; Lievens, Elke; Malik, Shweta; Imholz, Nicole; Lebeer, Sarah (Frontiers in Physiology, 2015)
The human body is colonized by a vast number of microorganisms collectively referred to as the human microbiota. One of the main microbiota body sites is the female genital tract, commonly dominated by Lactobacillus spp., in approximately 70% of women. Each individual species can constitute approximately 99% of the ribotypes observed in any individual woman. The most frequently isolated species are Lactobacillus crispatus, Lactobacillus gasseri, Lactobacillus jensenii and Lactobacillus iners. Residing at the port of entry of bacterial and viral pathogens, the vaginal Lactobacillus species can create a barrier against pathogen invasion since mainly products of their metabolism secreted in the cervicovaginal fluid can play an important role in the inhibition of bacterial and viral infections. Therefore, a Lactobacillus-dominated microbiota appears to be a good biomarker for a healthy vaginal ecosystem. This balance can be rapidly altered during processes such as menstruation, sexual activity, pregnancy and various infections. An abnormal vaginal microbiota is characterized by an increased diversity of microbial species, leading to a condition known as bacterial vaginosis. Information on the vaginal microbiota can be gathered from the analysis of cervicovaginal fluid, by using the Nugent scoring or the Amsel’s criteria, or at the molecular level by investigating the number and type of Lactobacillus species. However, when translating this to the clinical setting, it should be noted that the absence of a Lactobacillus-dominated microbiota does not appear to directly imply a diseased condition or dysbiosis. Nevertheless, the widely documented beneficial role of vaginal Lactobacillus species demonstrates the potential of data on the composition and activity of lactobacilli as biomarkers for vaginal health. The substantiation and further validation of such biomarkers will allow the design of better targeted probiotic strategies.